You are on page 1of 12

One-to-one and Inverse

Functions
A function y = f (x) with domain D is one-to-one on D
if and only if for every x1 and x2 in D, f (x1) = f (x2) implies
that x1 = x2.

A function is a mapping from its domain to its range


so that each element, x, of the domain is mapped to one,
and only one, element, f (x), of the range.

A function is one-to-one if each element f (x) of the


range is mapped from one, and only one, element, x,
of the domain.
Horizontal Line Test
A function y = f (x) is one-to-one if and only if
no horizontal line intersects the graph of y = f (x)
in more than one point.
y
Example: The function
y = x2 – 4x + 7 is not one-to-one (0, 7) (4, 7)
on the real numbers because the y=7
line y = 7 intersects the graph at 2
both (0, 7) and (4, 7). x
2
Example: Apply the horizontal line test to the graphs
below to determine if the functions are one-to-one.
a) y = x3 b) y = x3 + 3x2 – x – 1
y y
8 8

4 4

-4 4 -4 4
x x

one-to-one not one-to-one


Every function y = f (x) has an inverse relation x = f (y).

Function y = |x| + 1 Inverse relation x = |y| + 1


x y x y
2 2
1 3 1 3
0 2 0 2
-1 1 -1 1
-2 -2
Domain Range Range Domain
The ordered pairs of :
y = |x| + 1 are {(-2, 3), (-1, 2), (0, 1), (1, 2), (2, 3)}.
x = |y| + 1 are {(3, -2), (2, -1), (1, 0), (2, 1), (3, 2)}.
The inverse relation is not a function. It pairs 2 to both -1 and +1.
The ordered pairs of the function f are reversed to
produce the ordered pairs of the inverse relation.
Example: Given the function
f = {(1, 1), (2, 3), (3, 1), (4, 2)}, its domain is {1, 2, 3, 4}
and its range is {1, 2, 3}.
The inverse relation of f is {(1, 1), (3, 2), (1, 3), (2, 4)}.
The domain of the inverse relation is the range of the
original function.
The range of the inverse relation is the domain of the
original function.
The graphs of a relation and its inverse are reflections
in the line y = x.
Example: Find the graph of the inverse relation
geometrically from the graph of f (x) = ( x 3
− 2)
4
The ordered pairs of f are 3 y y=x
( x − 2)
given by the equation y = . 2
4
The ordered pairs of the inverse are
( y − 2)
3 x
given by x = . -2 2
4
-2
( y − 2)
3
( x 3 − 2)
x= y=
4 4
To find the inverse of a relation algebraically,
interchange x and y and solve for y.
Example: Find the inverse relation algebraically for the
function f (x) = 3x + 2.
y = 3x + 2 Original equation defining f
x = 3y + 2 Switch x and y.
3y + 2 = x Reverse sides of the equation.
( x − 2)
y= Solve for y.
3

To calculate a value for the inverse of f, subtract 2, then


divide by 3.
For a function y = f (x), the inverse relation of f
is a function if and only if f is one-to-one.

For a function y = f (x), the inverse relation of f


is a function if and only if the graph of f passes the
horizontal line test.

If f is one-to-one, the inverse relation of f


is a function called the inverse function of f.

The inverse function of y = f (x) is written y = f -1(x).


Example: From the graph of the function y = f (x),
determine if the inverse relation is a function and, if it
is, sketch its graph.
y y = f -1(x)
y=x
The graph of f passes
y = f(x)
the horizontal line test.
x
The inverse
relation is a function.

Reflect the graph of f in the line y = x to produce the


graph of f -1.
The inverse function is an “inverse” with respect to
the operation of composition of functions.
The inverse function “undoes” the function,
that is, f -1( f (x)) = x.

The function is the inverse of its inverse function,


that is, f ( f -1(x)) = x.
3
Example: The inverse of f (x) = x3 is f -1(x) = x.
3 3
f ( f(x)) = x = x and f ( f -1(x)) = ( 3 x )3 = x.
-1
x +1
Example: Verify that the function g(x) =
is the inverse of f(x) = 2x – 1. 2

( f ( x) + 1) ((2 x − 1) + 1) 2x
g( f(x)) = = = =x
2 2 2
x +1
f(g(x)) = 2g(x) – 1 = 2( ) – 1 = (x + 1) – 1 = x
2
It follows that g = f -1.